KINERJA DAN EMISI MESIN DIESEL 1 SILINDER BERBAHAN BAKAR CAMPURAN BIODIESEL NYAMPLUNG DAN ETANOL - Nasrul Ilminnafik; Atlanta Iwananda; Muh. Nurkoyim Kustanto; Rima Zidni Karimatan Nisa (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Research has been carried out on the effect of biodiesel and ethanol fuel mixtures on diesel engine performance and emissions. Ethanol (C2H5OH) is a type of alcohol that can improve the characteristics of biodiesel. The effect of ethanol on engine performance was investigated by adding B30 (a mixture of 30% nyamplung biodiesel (calophyllum inophyllum) and 70% petrodiesel). The concentration of ethanol added to B30 is 10% v/v which is called the B30E10 mixture. The composition of the fuel mixture is B0 (petrodiesel), B30, B30E10 and Pertadex. The research was conducted on a single cylinder four stroke diesel engine with a natural air system and coupled to a generator that functions as a dynamometer. Three times the test was carried out for each load applied to the engine varying from 0, 200, 400, and 600 W at a constant rotation speed of 1700 rpm. The research results that the constant engine speed method and variations in lamp load produce torque values (Nm) and effective power (kW) which tend to be the same between fuels, this happens because it is influenced by the governor mechanism. The highest fuel consumption occurred at the addition of 10% ethanol (B30E10). The lowest thermal efficiency occurs in B30E10. Exhaust emissions of carbon monoxide decreased with the addition of 10% ethanol.